E-learning motivation among student-athletes’ of Universiti Teknologi MARA (UiTM), Malaysia / Vincent Parnabas … [et al.] - Parnabas, Vincent; Abdullah, Nagoor Meera; Mohamed Shapie, Mohamad Nizam; Abdul Rahim, Mohamad Rahizam; Parnabas, Julinamary; Parnabas, Antoinette Mary; Isa, Mona; Idrakisyah, Mohamad (Faculty of Sports Science and Recreation, 2023)
The greatest challenge for educators during the pandemic Covid 19 situation today is to motivate their students to adopt e-learning. Therefore, it is important for lecturers in higher institutions to understand how to motivate their learners in choosing the types of motivation. Motivation refers to the concern with arousal, direction and persistence of behaviour towards the achievement of a specific goal, which classified into intrinsic and extrinsic. The objective of this study is to explore the types of motivation in adopting e-learning among the student-athletes of Sport Science and Recreation Faculty at University Technology MARA (UiTM), Malaysia. One hundred and twenty student t- athletes participated in this study. They were categorized into four ranking known as national, state, district and university based on their achievement in sports. The overall result showed that the student-athletes have the highest level of motivation in External Regulation (mean= 27.51), followed by Introjected Regulation (mean= 25.74), Identified Regulation (mean= 22.32), Amotivation (mean= 20.34), Intrinsic Motivation to Experience (mean= 17.17), Intrinsic Motivation to Know (mean= 15.31) and Intrinsic Motivation to Accomplish (mean= 12.55). Furthermore, national level athletes scored higher mean in both types of e-learning motivation except for Amotivation. In contrast, university ranking student-athletes scored the lowest on all the types of motivations for e-learning but highest in Amotivation. The findings obtained in this study supported by Self-Determination theory that e-learning involves the interaction of both intrinsic and extrinsic motivation.